2022
DOI: 10.1111/agec.12741
|View full text |Cite
|
Sign up to set email alerts
|

The effects of agricultural policy on supply and productivity: Evidence from differential changes in distortions

Abstract: Incentives in agriculture are highly distorted. It has long been argued that these distortions were a key explanation for differences in supply and productivity across countries, but the empirical evidence is limited. We revisit this issue using data on policy distortions across 63 countries for the period 1961-2011.We estimate the effects of differential changes in agricultural distortions across countries on supply and productivity. We highlight concerns in our analysis and previous work about endogeneity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…A group of researchers, namely Nathan P. Hendricks, Nelson B.Villoria, Aaron Smith and Matthieu Stigler in 2022 examined the effects of state agricultural policies on supply and productivity. Thus, confirming the thesis of Nobel laureate Theodore V. Schultz (1979) about the negative consequences of protectionism in agriculture, the researchers concluded that "the elimination of destructive state intervention increases productivity", and the strengthening of economic incentives encourages improved agricultural technologies and innovations [6]. In the scope of view of Ukrainian scientists and economists, the issue of state financial support for the agricultural sector of Ukraine's economy remains relevant.…”
Section: Relevant Researchmentioning
confidence: 59%
“…A group of researchers, namely Nathan P. Hendricks, Nelson B.Villoria, Aaron Smith and Matthieu Stigler in 2022 examined the effects of state agricultural policies on supply and productivity. Thus, confirming the thesis of Nobel laureate Theodore V. Schultz (1979) about the negative consequences of protectionism in agriculture, the researchers concluded that "the elimination of destructive state intervention increases productivity", and the strengthening of economic incentives encourages improved agricultural technologies and innovations [6]. In the scope of view of Ukrainian scientists and economists, the issue of state financial support for the agricultural sector of Ukraine's economy remains relevant.…”
Section: Relevant Researchmentioning
confidence: 59%